Individual and combined effects of heavy metals on 'survival aud biochemistry of Oreoclzromis mossambicus - James, R; Sampath, K; Sivakumar, V; Manthiramoorthy, S (Indian Journal of Fisheries, 2011)
Information about thecombined effects of heavy metals on survivalaocl biochemistry of fISh being ~ty, thepreSent swdy on effects of copper, zinc andcadmium on survival and biochemical compositiOnof the fish Oreochromis mossambicus.was undertaken.